2014
DOI: 10.1186/s12870-014-0198-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic development of starch granules and the regulation of starch biosynthesis in Brachypodium distachyon: comparison with common wheat and Aegilops peregrina

Abstract: BackgroundThorough understanding of seed starch biosynthesis and accumulation mechanisms is of great importance for agriculture and crop improvement strategies. We conducted the first comprehensive study of the dynamic development of starch granules and the regulation of starch biosynthesis in Brachypodium distachyon and compared the findings with those reported for common wheat (Chinese Spring, CS) and Aegilops peregrina.ResultsOnly B-granules were identified in Brachypodium Bd21, and the shape variation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 64 publications
5
50
1
Order By: Relevance
“…Evidence suggests that compound starch granules represent the ancestral state in the Poaceae, e.g., Sorghum italica is the earliest diverging lineage within the PACMAD clade, and is the only member of this group with compound granules in the endosperm ( [1,[402][403][404] (see Figure 1) and simple or bimodal granules occur in only more recently diverged lineages. Brachypodium is phylogenetically closer to wheat (bimodal starch granules) than maize (simple starch granules) [405], yet shows only small B-type (and C-type) granules in the endosperm [398,406]. In the grasses and cereals of the Festucoid family, large lenticular-shaped A-type granules (10-35 µm diameter) are formed early in endosperm development, whilst the smaller, near-spherical B-type granules (averaging 5-9 µm in diameter) are formed later [407][408][409].…”
Section: Starch Granule Growth Size and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that compound starch granules represent the ancestral state in the Poaceae, e.g., Sorghum italica is the earliest diverging lineage within the PACMAD clade, and is the only member of this group with compound granules in the endosperm ( [1,[402][403][404] (see Figure 1) and simple or bimodal granules occur in only more recently diverged lineages. Brachypodium is phylogenetically closer to wheat (bimodal starch granules) than maize (simple starch granules) [405], yet shows only small B-type (and C-type) granules in the endosperm [398,406]. In the grasses and cereals of the Festucoid family, large lenticular-shaped A-type granules (10-35 µm diameter) are formed early in endosperm development, whilst the smaller, near-spherical B-type granules (averaging 5-9 µm in diameter) are formed later [407][408][409].…”
Section: Starch Granule Growth Size and Morphologymentioning
confidence: 99%
“…Three major starch granule morphologies exist within the Poaceae: (1) compound granules, which are made up of tightly packed polygonal granules arranged in spherical-like structures with membranous cross walls termed septa, and are typically found in rice and other members of the Ehrhartoideae [258] and Bambusoideae [396]; (2) simple granules, discrete granules of varying size (2-30 µm) and shape, e.g., polyhedral, lenticelullar, or spherical, and found in maize and sorghum [392,397]; and, (3) granules with a bimodal size distribution, typically a mix of small spherical (B-type) and large lenticellular (A-type) granules, and are generally found in the Festucoid family of temperate grasses, such as goatgrass (Aegilops peregrina Hack. ), and cereals such as wheat, barley, and rye [398][399][400][401]. Evidence suggests that compound starch granules represent the ancestral state in the Poaceae, e.g., Sorghum italica is the earliest diverging lineage within the PACMAD clade, and is the only member of this group with compound granules in the endosperm ( [1,[402][403][404] (see Figure 1) and simple or bimodal granules occur in only more recently diverged lineages.…”
Section: Starch Granule Growth Size and Morphologymentioning
confidence: 99%
“…Several studies have shown the Brachypodium starch granules are small in size and are not bimodally distributed (Chen et al 2014a;Guillon et al 2012;Hands et al 2012;Opanowicz et al 2011), although Tanackovic et al (2014) reported a bimodal population of Brachypodium granules consisting of small B-type (2.5-10 μm) and very small C-type (0.5-2.5 μm). The large A type granules, a typical type in cereals, are absent in Brachypodium.…”
mentioning
confidence: 98%
“…It has been observed that the starch is distributed along a gradient in the Brachypodium seed, being more abundant in the proximal end of the endosperm than at the distal end which is away from embryo, and is restricted in the central zone of the endosperm at the distal end (Trafford et al 2013). The starch transiently accumulated in the pericarp at an early developmental stage, and started to accumulate in the endosperm after cellularization (Chen et al 2014a;Guillon et al 2012;Trafford et al 2013). Starch granules appeared at 15 DAF and were apparently distributed around the periphery of endosperm cells at 17 DAF, and afterwards took over all the spaces excluding the fused vacuoles in mature seeds (Guillon et al 2012).…”
mentioning
confidence: 98%
See 1 more Smart Citation